Penerapan Teknologi Las Gesek (Friction Welding) Dalam Proses Penyambungan Dua Buah Pipa Logam Baja Karbon Rendah - Sanyoto, Budi Luwar; Husodo, Nur; Setyawati, Sri Bangun; Mursid, Mahirul (Jurnal Energi Dan Manufaktur; Vol 5 No 1 (2012): Oktober 2012)
Kata kunci: waktu gesek, las gesek, tekanan tempa, baja karbon rendah, pipa air Abstract The welding process of the carbon steel pipe will be abit difficult since during welding it is needed rotary movement of the pipe in order to the operator easily to join the welding. This difficulty can be overcome by applying friction welding technology. This method is strongly influenced by friction time, rotation velocity and pressure of the pressing. Therefore it is needed the research to joint the carbon steel pipe by applying friction welding. The variation time for the friction welding test were 15, 20, 25, 30 and 35 second. The process parameters were keep constant. The friction welding machine was operated with 4125 rpm, friction pressure 15 kg/cm2 and pressure about 70 kg/cm2.The specimen obtained was tested for metallographic, hardness test. The metallography test was done recognize the microstructure and the hardness test was conducted to obtain the hardness distribution in the original material, in the HAZ region, and in the welding metal. Analyses for the value of hardness in the three region namely, origin metal, HAZ, and welding metal will be related to the change in microstructure.The longer the time for the friction, the temperature increase respectively. But the increase the temperature affect on the upset value become larger and the sample become shorter. The research for joining with friction welding 4125 rpm, friction pressure 15 kg/cm2 and thresure 70 kg/cm3 can be concluded that frinction time that is recomended is 35 second.Friction welding method can be applied for the joining low carbon steel pipe. The microstructure in the joining was found not significant change that mean there is no change in mechanical properties
Keywords: friction time, Pressure press, low carbon steel, water pipe